Evaluation of Cardiac Findings in Mucopolysaccharidosis Type III Patients - Berrak Bilginer Gürbüz; Ebru Aypar; Dursun Alehan; Ayşegül Tokatlı; Turgay Coşkun; Ali Dursun; H. Serap Sivri (Galenos Yayinevi, 2021)
Aim:To investigate cardiac involvement in patients diagnosed with mucopolysaccharidosis type III (MPS III) in a university hospital in Turkey.Materials and Methods:This descriptive cross-sectional study was performed in a university hospital by examining the files of 49 MPS III patients who were admitted between January 1998 and December 2019.Results:The mean age of the participants was 12.24±5.21 years (range: 1-26). The mean age at which the patients underwent echocardiography was 6.90±4.82 years. MPS IIIA, IIIB, IIIC, and IIID subtypes were present in 24 (49.0%), 19 (38.8%), 5 (10.2%), and 1 (2.0%) patient, respectively. Among the MPS III patients who had echocardiographic evaluation (n=44), 32 patients (72.7%) had pathological cardiac findings, while 12 patients (27.3%) had normal cardiac findings on echocardiographic examination. The most common cardiac pathologies were those related to mitral valve [valve insufficiency 52.3% (n=27), valve thickening 43.2% (n=25), and prolapse 38.6% (n=23)]. Tricuspid insufficiency (34.8%, n=8) was seen only in MPS IIIA. Mitral insufficiency and aortic valve thickening were significantly more common among females (p=0.014, p=0.025, respectively).Conclusion:Patients with MPS III should be closely monitored for cardiac pathologies and especially mitral valve insufficiency, which are more prevalent among females.